Bilib ka ba? Bili na! factors affecting television viewing and consumer behavior - Arinuelo, Lileth L.
This study examines the difference in advertisement viewing, television viewing, and buying behavior as affected by the individual's demographic and socio-economic background. The researcher conducted a one-shot survey in UP Village and Krus na Ligas. There were one hundred residents representing UP Village and another one hundred for Krus na Ligas. The respondents were chosen using systematic random method. Krus na Ligas and UP Village were selected areas for the study because of the discrepancy in the socio-economic status based on habitat. This study found that Krus na Ligas and UP Village respondents have almost the same viewing habits. Both samples are moderate viewers. Because most of them are student or regular workers, television viewing happens in the evening. Krus na Ligas respondents go home around 6-8 pm while those in UP Village are at home a little later (8-10 pm). Both groups watch television to relax and regard it as a good activity. They both like watching in fact, they consider it as a hobby and interest. They both watch a moderate number of commercials (20-30) because of average number of hours watching television (2-5 hours a day). They both are passive in their commercial viewing but they attend to advertisements when they have plans to purchase the product. Both admitted that they are persuaded by advertisements to buy certain products. Food was the top choice for purchase for both samples. This is understandable since this is the basic need of everybody. However, Krus na Ligas respondents answered beverages as second and beauty products as third. Beverages can be considered necessity and beauty products are also a predictable answer because the sample is composed mostly of female teenagers. This study also found out that respondents who are older, have high educational background, high income, and prestigious jobs are the ones who dislike television watching and do not regard it as a good activity because this interferes with their work. Prestigious jobs are associated with high income and this occupation requires solid background in education. The work usually takes more time than other 8-hour jobs and this means they are busier people. Television viewing remains in the moderate level because high usage means interruption form other activities. And also, they could afford other sources of information and entertainment. Television is not the only hobby and interest of this people because they can afford other forms of leisure. Also, they are not attentive to TV and the instances they usually attend are when there is a new product being advertised and when they have plans to purchase. Male and female respondents did not differ in their answers in almost all variables except for instances when commercials get their attention and buying habits. Males answered superficial reasons for liking the commercial while females scored high in 'plans for purchase.' This means that males see the commercials for its entertainment value. Their buying habits also reflected the traditional dichotomy of male and female products. While males purchase sport goods, female include beauty products in their shopping lists. Married and single respondents have similar answers except for attentiveness in commercials, instances for attentiveness, and buying habits. Single respondents are more attentive and they attend to commercials in the instance of purchase plans. They also buy more products regularly. This answer can be related to their financial capacity. Because their earning is spent only at themselves, they could afford to purchase more. Also commercial viewing is seen as come form of market, which presents more products to consume.